Cultivation technology for sweet pepper in a greenhouse and an open field - O.N. Pishnaya; M.I. Mamedov; E.A. Dzhos (Овощи России)
Sweet pepper, as one of the most important sources of vitamins and antioxidants, is a very necessary vegetable in human's food. In the article the detailed description of varieties and hybrids is given concerning also to the principals of pepper cultivation technology.